IRRIGACIYA KANALLARÍNDA SUWDÍ OPTIMAL BÓLISTIRIWDIŃ ZÁRÚRLI SHÁRTLERIN KONVEKCIYA-DIFFUZIYA MODELI TIYKARÍNDA ISLEP SHÍǴÍW - Qudaybergenov, A.A.; Ametova, A.E.; Eshbaev, A.J. (SCIENCE and SOCIETY, 2024)
The article develops the necessary conditions for the optimal distribution of water resources to consumers, taking into account the boundary conditions of irrigation canals and the associated conditions of canal sections.
Keywords: optimal control; necessary conditions for optimality; water distribution; mathematical model